Banquet: Short and Fast Signatures from AES - Baum, Carsten; Guilhem, Cyprien Delpech de Saint; Kales, Daniel; Orsini, Emmanuela; Scholl, Peter; Zaverucha, Greg (PKC 2021, 2021)
In this work we introduce Banquet, a digital signature scheme with post-quantum security, constructed using only symmetric-key primitives. The design is based on the MPC-in-head paradigm also used by Picnic (CCS 2017) and BBQ (SAC 2019). Like BBQ, Banquet uses only standardized primitives, namely AES and SHA-3, but signatures are more than 50% shorter, making them competitive with Picnic (which uses a non-standard block cipher to improve performance). The MPC protocol in Banquet uses a new technique to verify correctness of the AES S-box computations, which is efficient because the cost is amortized with a batch verification strategy. Our implementation and benchmarks also show that both signing and verification can be done in under 10ms on a current x64 CPU. We also explore the parameter space to show the range of trade-offs that are possible with the Banquet design, and show that Banquet can nearly match the signature sizes possible with Picnic (albeit with slower, but still practical run times) or have speed within a factor of two of Picnic (at the cost of larger signatures).